The best digital marketing campaigns in the world II - Ryan, Damian (Kogan Page, 2014)
In the second collection of The Best Digital Marketing Campaigns in the World, bestselling author Damian Ryan presents an international showcase of the most successful digital marketing campaigns in recent history. Full of behind-the-scenes insights into campaign strategy, implementation and results, it explores how businesses and agencies large and small have harnessed social media, blogs, video, email, mobile and search to boost their brand and attract customers. Covering a wide range of world-class, award-winning campaigns including Redbull and Stratos, Evian's 31 ways to live young, and Stu.